Europe's Invisible Migrants - Smith, Andrea (Europa, 2002)
Following the decolonization movements that swept the globe after World War II, between four and six million people were 'returned' to Europe from the colonies. From an exporter of people, Europe turned to a site of immigration for the first time in the twentieth century. Until now, these migrations have been overlooked as scholars have highlighted instead the parallel migrations of former 'colonized' peoples. Europe's Invisible Migrants corrects this bias. This multidisciplinary volume presents essays by prominent sociologists, historians, and anthropologists on their research with these 'invisible' migrant communities. Their work highlights the experiences of colonists returning to France, Portugal and the Netherlands, the intersection of race, citizenship, and colonial ideologies, and the ways these migrations reflect the return of the 'colonial' to Europe. This volume offers fresh insights into immigration, racism and ethnic conflict in post-colonial Europe by presenting colonial repatriates as another 'immigrant' population.